Comparative Experimental and Computational Studies of Hydroxyl and Sulfate Radical-Mediated Degradation of Simple and Complex Organic Substrates - Chen, Yufan; Vu, Huong Chi; Miller, Christopher J.; Garg, Shikha; Pan, Dai; Waite, T. David (Environmental science & technology, 2022)
Persulfate (PS)-based advanced oxidation processes (AOPs) have been promoted as alternatives to H2O2-based AOPs. To gauge the potential of this technology, the PS/Fe(II) and Fenton (H2O2/Fe(II)) processes were comparatively evaluated using formate as a simple target compound and nanofiltration concentrate from a municipal wastewater treatment plant as a complex suite of contaminants with the aid of kinetic modeling. In terms of the short-term rate and extent of mineralization of formate and the nanofiltration concentrate, PS/Fe(II) is less effective due to slow Fe(II)/Fe(III) cycling attributable to the scavenging of superoxide by PS. However, in the concentrate treatment, PS/Fe(II) provided a sustained removal of total organic carbon (TOC), with ∼81% removed after 7 days with SO4 •– consistently produced via homolysis of the long-life PS. In comparison, H2O2/Fe(II) exhibited limited TOC removal over ∼57% after 10 h due to the futile consumption of H2O2 by HO•. PS/Fe(II) also offers better performance at transforming humic-like moieties to more biodegradable compounds as a result of chlorine radicals formed by the reaction of SO4 •– with the matrix constituents present in the concentrate. The application of PS/Fe(II) is, however, subject to the limitations of slow oxidation of organic contaminants, release of sulfate, and formation of chlorinated byproducts.